SOUTH KOREA'S FOREIGN POLICY: UNVEILING FACTORS IN HALAL INDUSTRY DEVELOPMENT - Konety, Neneng; Nidatya, Nurfarah; Akim (Indonesian Journal of International Relations, 2023)
This study aims to analyze the factors that underlie South Korea's foreign policy regarding halal industry development. The decision-making theory proposed by Richard C. Snyder, Bruck, and Burton Sapin is the theoretical framework employed, while employing a qualitative approach, literary study and interview techniques. The research findings reveal that the formulation of South Korea's foreign policy in the halal industry development can be explained through various variables. In conclusion, South Korea's halal industry policy draws from decision-making theory, considering internal factors like the Muslim population, economic goals, and innovation. Social structures and external influences, such as global demand and Muslim tourism, play significant roles.